Effects of short-term physical training on the liver IGF-I in diabetic rats - Curiacos de Almeida Leme, Jose Alexandre; Gomes, Ricardo Jose; Rostom de Mello, Maria Alice; Luciano, Eliete (Taylor & Francis Ltd, 2007)
To investigate the influence of short-term physical training on IGF-I concentrations in diabetic rats, male wistar rats were distributed into four groups: sedentary control, trained control, sedentary diabetic and trained diabetic. Diabetes was induced by Alloxan (32 mg/kg b.w.) and training protocol consisted of swimming 1 h/day, 5 days/week, during 4 weeks, supporting 5% b.w. At the end of this period, rats were sacrificed and blood was collected for determinations of serum glucose, insulin, albumin, IGF-I and hematocrit. Liver samples were used to determine glycogen, protein, DNA and IGF-I concentrations. Diabetes reduced insulin and IGF-I concentrations in blood and liver protein, ratio protein/DNA and IGF-I concentrations in liver and increased glycemia. Physical training reduced serum glucose and recovered hepatic glycogen stores in diabetic rats and reduced serum and liver IGF-I concentrations. In conclusion, short-term physical training improved the metabolic conditions of diabetic rats, despite of impairing liver and blood IGF-I concentrations.
Keywords: diabetes; insulin-like growth factor-I; liver and training; DNA